Effectiveness of Implementing Standard Operating Procedures and Job Safety Analysis in Risk Management for Pier Pile Driving Activities (Case Study on Pier Development Pile Driving at KSP BMN Tanjung Wangi Banyuwangi) - Sudarta, Sudarta; Candra, Candra; Maniza, Lalu Hendra (Business Management, 2026)
Occupational safety and health (OSH) is a fundamental right of workers that must be guaranteed by every employer by ensuring effective and professional risk management. In the context of the BMN Tanjung Wangi pier pile driving project in Banyuwangi, the implementation of Standard Operating Procedures (SOP) and Job Safety Analysis (JSA) plays a crucial role in controlling potential occupational hazards. This study aims to evaluate the effectiveness of SOP and JSA implementation in risk management during the project. A qualitative approach was used in this study, with data collection through in-depth interviews and field observations of parties directly involved in the project, such as planners, supervisors, technicians, and workers. The results of the study show that PT Lombok Karya Perkasa (LKP) has successfully developed and implemented SOPs and JSAs as effective work guidelines for identifying, assessing, and controlling risks. The use of SOPs and JSAs significantly helps in managing hazards, such as the risk of falling, being hit by materials, and equipment damage, which have the potential to cause work accidents. With consistent implementation, it is hoped that the pile driving project can run more safely and efficiently.